BEBAN PAJAK TANGGUHAN, LEVERAGE, ASIMETRI INFORMASI TERHADAP MANAJEMEN LABA - Prakas Buai Basrian; Reni Oktavia; Chara Pratami Tidespania Tubarat (Faculty of Economics and Business, 2021)
The purpose of this study was to examine the effect of deferred tax expense, leverage, and information assimilation on earnings management. This study uses secondary data with a population of companies registered in the Consumer Goods Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The method used to determine the sample using purposive sampling. It consists of 18 manufacturing companies in the Consumer Goods industry with 90 samples. The analytical method used is descriptive data analysis. The results of hypothesis testing show that Deferred Tax Expenses have no effect on earnings management, Leverage has a positive effect on corporate earnings management and information assurance has no effect on corporate earningsmanagement.